2021
DOI: 10.3390/biophysica1020007
|View full text |Cite
|
Sign up to set email alerts
|

Nanomarker for Early Detection of Alzheimer’s Disease Combining Ab initio DFT Simulations and Molecular Docking Approach

Abstract: The tau protein is considered an important qualitative and quantitative biomarker for Alzheimer’s disease in its asymptomatic phase. In 2011, biomarkers were suggested by the National Institute on Aging-Azheimer’s Association as a new criterion for the early diagnosis of Alzheimer’s disease. Thus, highlighting the non-existence of theoretical research on the subject, we investigated the binding interaction properties between phosphorylated tau protein and a theoretically modeled ligands constituted by the full… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…After the fragmentation of each amino acid, to calculate the interaction energy between the receptor and the ligand, two methods were applied: density functional theory (DFT) formalism [ 34 ] and the generalized gradient approximation (GGA) functional B97D, computed by Gaussian 16 software package. It has been previously suggested that this GGA-type density functional is an accurate and efficient QM method [ 35 ], especially when dispersion forces are an important element, often valid for large systems.…”
Section: Methodsmentioning
confidence: 99%
“…After the fragmentation of each amino acid, to calculate the interaction energy between the receptor and the ligand, two methods were applied: density functional theory (DFT) formalism [ 34 ] and the generalized gradient approximation (GGA) functional B97D, computed by Gaussian 16 software package. It has been previously suggested that this GGA-type density functional is an accurate and efficient QM method [ 35 ], especially when dispersion forces are an important element, often valid for large systems.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, Schopf and co-workers reported the DFT simulation combined with molecular docking approach for the detection of AD biomarkers. 37 They considered the tau protein as an AD biomarker and studied its interaction with theoretically modeled ligands. Apart from that, to the best of our knowledge, there is hardly any study that reported the design of a biosensor capable of detecting AD fingerprint VOCs for early diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…There are very few computational studies that dealt with the early diagnosis of AD. For instance, Schopf and co-workers reported the DFT simulation combined with molecular docking approach for the detection of AD biomarkers . They considered the tau protein as an AD biomarker and studied its interaction with theoretically modeled ligands.…”
Section: Introductionmentioning
confidence: 99%